The Influence of Prior Knowledge on Perception and Action: Relationships to Autistic Traits - Buckingham, Gavin (J Autism Dev Disord, 2016)
Autism is characterised by a range of perceptual and sensorimotor deficits, which might be related to abnormalities in how autistic individuals use prior knowledge. We investigated this proposition in a large non-clinical population in the context of the size-weight illusion, where individual’s expectations about object weight influence their perceptions of heaviness and fingertip forces. Although there was no relationship between autistic traits and the magnitude of the illusion, we observed an inverse relationship between AQ scores and how expectations influenced initial fingertip force application. These findings provide a novel dissociation between how perceptual and sensorimotor processes are related to autistic traits, and suggest that, autistic traits might explain some of the variance surrounding how individuals grip and lift objects.